OPTIMALISASI PROFESIONALISME AUDITOR MELALUI UNDANG-UNDANG NO. 5 TAHUN 2011 - Hatta H Atika Jauharia (Dinamika Akuntansi Keuangan dan Perbankan, 2012)
Public accountant has an important role to the business. Their opinion through audit statement has been used by stakeholder of the company to make economic decision. Audit statement expected to improve the quality and credibility of the financial statement released by management. But after Enron scandal that involved auditor of Arthur Andersen, one of the biggest public accountant firm in the world, professionalism of auditor was questioned. Implication of the scandal, America released Sarbanes-Oxley Act in 2002, while Indonesia has released UU No. 5 in 2011 to regulate public accountant profession, that can increase professionalism of public accountant at the same time protects public accountant and public interest. Key words:   public accountant, UU No. 5 tahun 2011, professionalism, Enron scandal, financial statement, and audit statement.